The Macroeconomics of Epidemics. (7th April 2021) - Eichenbaum, Martin S; Rebelo, Sergio; Trabandt, Mathias
Abstract: We extend the canonical epidemiology model to study the interaction between economic decisions and epidemics. Our model implies that people cut back on consumption and work to reduce the chances of being infected. These decisions reduce the severity of the epidemic but exacerbate the size of the associated recession. The competitive equilibrium is not socially optimal because infected people do not fully internalize the effect of their economic decisions on the spread of the virus. In our benchmark model, the best simple containment policy increases the severity of the recession but saves roughly half a million lives in the United States.